A health system in economic crises: A case study from Iceland. Issue 2 (March 2013) - Olafsdottir, Anna Elisabet; Allotey, Pascale; Reidpath, Daniel D.
Background : There has been a lack of systematic inquiry into how governments respond during times of crises, how well these responses comply with good governance, and how they affect health systems. The aim of this study was to analyse the reactions of the Icelandic health system during the first 7 months of the economic crisis in 2008. Methods : The grounded theory approach was used in data sampling, collection, and data analysis. Secondary data were collected from parliamentary documents, news, and health discussions in two of the largest newspapers in Iceland. Primary data were collected through interviews with key stakeholders in the health sector. Atlas.ti. 5.2 was used to analyse the data. Results : The health sector's first response to the crisis was to close and merge wards on hospitals as well as making structural changes to reduce the overhead costs in healthcare institutions. The Minister of Health attempted to introduce radical changes but because of failures in good governance practices, such as a lack of transparency and fair participation together with a lack of supporting documents, the proposed changes were not executed. Conclusions : Economic crises are a critical test of health systems' resilience. The manner in which governance practices, together with strong stewardship, influence the ability of the health system to adapt to changes and reorganise without causing stress, confusion, or anger and without changing its basic structure and function are important, and open to robust evaluation.